Analisis Sajian Buku Ajar Fisika SMA Kelas X Semester 1 Terkait Komponen Science, Technology, Engineering, Mathematics (STEM) - Laura Aliyah Agnezi; Nyswatul Khair; Sinta Yolanda (JURNAL EKSAKTA PENDIDIKAN (JEP), 2019)
An important problem in the 21st century is the integration of information and communication technology in learning. Because teachers and students must be prepared to keep abreast of increasingly sophisticated times. STEM is a learning that integrates science (science), technology (technology), engineering (engineering), and mathematics (mathematics). STEM provides learning through the process of solving problems in everyday life in order to enhance students' creative abilities. STEM learning aims to improve the ability of students to compete with the surrounding environment and globally, both in science and able to innovate technological products. Currently there are many textbooks in circulation with various publishers. For this reason, it is necessary to find out whether the outstanding textbooks have been able to facilitate the implementation of the STEM approach in learning. The solution to this problem is to analyze the extent to which the textbook meets the STEM component. This type of research is a descriptive research with a qualitative approach. The population of data in this research were all physics textbooks for class X semester 1 high school. The samples in this research were five books used in learning physics in class X semester 1 high school. The data in this research were taken using a research instrument which had 4 components which were elaborated into 19 assessment items and data collection techniques used are through observation. The results of this research indicate that the average suitability obtained for each book that is in textbook 1 has a value of 88 with a category in accordance with the STEM component. In textbook 2 has a value of 85 with a category in accordance with the STEM component. In textbook 3 with a value of 72 with categories according to the STEM component. Textbook 4 with a value of 77 with categories according to the STEM component. Finally in textbook 5 with a value of 85 with a category very much in accordance with the STEM component